Pharmacokinetics of dolutegravir with and without darunavir/cobicistat in healthy volunteers. (1st October 2018) - Elliot, Emilie R; Cerrone, Maddalena; Else, Laura; Amara, Alieu; Bisdomini, Elisa; Khoo, Saye; Owen, Andrew; Boffito, Marta
Abstract: Background: Dolutegravir combined with darunavir/cobicistat is a promising NRTI-sparing and/or salvage strategy for the treatment of HIV-1 infection. Methods: This Phase I, open-label, 57 day, crossover, pharmacokinetic (PK) study, enrolled healthy volunteers aged 18–65 years, who were randomized to one of two groups. Group 1 received dolutegravir (50 mg) once daily for 14 days followed by a 7 day washout, then a 14 day dolutegravir/darunavir/cobicistat (DTG/DRV/COBI) once-daily co-administration period followed by a 7 day washout and finally a 14 day period of darunavir/cobicistat (800/150 mg) once daily. Group 2 followed the same sequence starting with darunavir/cobicistat and concluding with dolutegravir. Each group underwent intensive PK sampling over 24 h on day 14 of each drug period and DTG/DRV/COBI concentrations were measured using validated LC-MS/MS methods. Results: Twenty participants completed all PK phases. Thirteen were female and median age and BMI were 33.5 years and 27 kg/m 2 . Dolutegravir geometric mean ratios (GMR, DTG/DRV/COBI versus dolutegravir alone) and 90% CI for C max, AUC0–24 and C 24 were 1.01 (0.92–1.11), 0.95 (0.87–1.04) and 0.9 (0.8–1.0), respectively. Darunavir GMR (DRV/COBI/DTG versus darunavir/cobicistat alone) and 90% CI for C max, AUC0–24 and C 24 were 0.90 (0.83–0.98), 0.93 (0.86–1.00) and 0.93 (0.78–1.11), respectively. No grade 3 or 4 adverse events or laboratory abnormalities were observed. Conclusions: Concentrations of dolutegravir and darunavir, when boosted with cobicistat, decreased by <10% during co-administration, suggesting this combination can be prescribed safely in the treatment of HIV-1, with no adjustment to current guideline-recommended dosages.